Etude d’un phénomène de discrimination esthétique : la « naquez » au Mexique - Philippe Schaffhauser (Amnis)
Drawing from the later Wittgenstein, author of the Philosophical Investigations, according to which words have palpable effects, the goal of this article is to present and interrogate the Mexican cultural category of the naco, with the related terms naquez and naquisa. The meaning of this cluster of terms is more or less equivalent to the French vernacular plouc. It is defined by a sort of “bad taste,” but also carries a racializing charge. The article also reflects on the sociological uses of these terms. The main result of this interpretive work, which gathers sociolinguistic, historic, anthropological, and philosophical concerns analytically, is to begin to throw into relief another facet of Mexican identity. The « naco » concept forms part of the relations of power and meaning that structure much of Mexican society today, and is something we might identify both as belonging phenomena of aesthetic discrimination, and also as an antechamber to an overt racism that is social as well as cultural. Finally, if every Mexican is « a little bit naco », and each considers his neighbor or brother-in-law to be more so, it is worth pointing out that this matter of aesthetic tastes is a universal datum.